Evaluation of the flow distribution system influence on mixing efficiency in a fluidized bed for low-size Geldart B particles: A case study using CFD - Diana I. González-Arango; Bernardo Herrera (South African Journal of Chemical Engineering)
Hydrogen is emerging as one of the alternative fuels for replacing fossil fuels within a sustainable energy transition framework. One of the technologies for hydrogen production is Chemical Looping Reforming (CLR), which stands out for its ability to capture and store CO₂. However, the performance of the CLR process for hydrogen production largely depends on the efficiency of energy and mass transfer between the gas and solid phases of the reaction. To increase this efficiency, fluidized bed reactors promote interaction between both phases, which depends on the velocity and the gas phase distribution system. The latter must be compatible with the design of the geometry and size of the solid oxygen carrier particles (SOC), which are mainly in the low-size Geldart B range. This study aims to examine how the geometry of three different gas phase distributors in a fluidized bed reactor affects the pressure drop and the mixing index of low-size Geldart B particles. The three geometries considered are a perforated plate with 0.8 mm diameter holes, a No 400-mesh sieve, and a porous frit with a porosity of 0.76. The study is based on the application of a CFD numerical model, experimentally validated, which employs the Eulerian multiphase method to model gas-solid interaction, the realizable k−ε model to describe the turbulence and the Syamlal-O'Brien model to simulate the drag phenomenon. The accuracy of the results was verified using the grid convergence index (GCI) based on Richardson's extrapolation method. The study's primary results showed that CFD simulations were consistent with the experimental data, with a <10 % percentage variation. Furthermore, the pressure drop with the porous frit demonstrated a significant improvement in gas flow uniformity and operational efficiency compared to the other two plates, which produced uneven distributions that reduced efficiency. Moreover, the mixing index was higher in the porous frit, improving up to 0.9 % compared to the retaining mesh and 9.5 % compared to the perforated plate. Therefore, the main conclusion was that the porous frit is a viable method for improving the efficiency of the fluidized bed in terms of the pressure drop, mixing of micrometric-scale particles, and generating turbulence to promote heat and mass transfer between the gas and solid phases.